ANALISIS KETERWAKILAN 30 PERSEN PEREMPUAN PADA PEMILU 2024 DITINJAU DALAM PERSEPEKTIF HUKUM KELUARGA ISLAM - Rahmawati, Nirmala Eka (Universitas Al-Amien Prenduan, 2024)
Women's participation in legislative elections is one of the issues in Indonesia's political dynamics. Although the data shows an increase in percentage compared to the results of the previous elections, women's representation in the 2024 elections has not yet reached 30 percent. This paper shows that women's representation in parliament is still low in terms of candidates elected to the Senayan, cultural factors, religious stigma, and political structures are the main obstacles. However, affirmative action policies have succeeded in increasing the number of women in parliament. The research also reveals that Islamic family law plays an important role in shaping women's participation through aspects such as marriage, inheritance, and roles within the family. Through the integration of Islamic family law perspectives and feminist theories, this research aims to identify gaps in understanding regarding women's participation in the 2024 elections and devise holistic solutions to increase women's participation in the political process in Indonesia.